Bridging cognitive screening tests in neurologic disorders: A crosswalk between the short Montreal Cognitive Assessment and Mini‐Mental State Examination. Issue 8 (23rd February 2017) - Roalf, David R.; Moore, Tyler M.; Mechanic‐Hamilton, Dawn; Wolk, David A.; Arnold, Steven E.; Weintraub, Daniel A.; Moberg, Paul J.
Abstract: Introduction: To provide a crosswalk between the recently proposed short Montreal Cognitive Assessment (s‐MoCA) and Mini‐Mental State Examination (MMSE) within a clinical cohort. Methods: A total of 791 participants, with and without neurologic conditions, received both the MMSE and the MoCA at the same visit. s‐MoCA scores were calculated and equipercentile equating was used to create a crosswalk between the s‐MoCA and MMSE. Results: As expected, s‐MoCA scores were highly correlated (Pearson r = 0.82, P < .001) with MMSE scores. s‐MoCA scores correctly classified 85% of healthy older adults and 91% of individuals with neurologic conditions that impair cognition. In addition, we provide an easy to use table that enables the conversion of s‐MoCA score to MMSE score. Discussion: The s‐MoCA is quick to administer, provides high sensitivity and specificity for cognitive impairment, and now can be compared directly with the MMSE.